Automated Second-Order Elastic Analysis for Steel Space Frames - Folse, Michael D.; Harris, Barton H. (Engineering Journal, 1990)
The magnification of bending moments and deflections due to interaction between axial compression and transverse loads is popularly known as second-order elastic effects. The American Institute of Steel Construction (AISC) specifications for building construction require inclusion of second-order elastic effects in the design of steel structures. In the past, these effects have been approximated by multiplying moments obtained through a linear analysis by a magnification factor. It is simpler and generally more accurate to compute second-order elastic effects within a displacement method computer analysis program. Several different approaches to automated computation are possible. Two methods of including second-order elastic effects in space frame analysis are described herein along with a FORTRAN computer program which executes the stiffness modification method while checking steel wide flange beam-columns for compliance with the AISC Load and Resistance Factor Design (LRFD) Specification.